Migration of Pastoralists in Africa: Reflections on Practical and Policy Implications (African Human Mobility Review, 2021)
In recent years, there has been increased migration of pastoralists fromcountries in Central and West Africa into Nigeria. Such movements aresupported by the ECOWAS Transhumance Protocol and the NigerianConstitution respectively. The movement of pastoralists has been associated withmulti-dimensional practical and policy implications. This paper reflects on thepolicy implications of the migration of pastoralists across and within the bordersof Nigeria and presents pointers to the areas for future policy intervention andresearch. The paper relied on existing policies like the ECOWAS TranshumanceProtocol, the Nigerian Constitution and the Open Grazing Prohibition Lawenacted by the Benue State government to draw inferences about the relevanceand effectiveness of such laws in Nigeria. Interviews with farmers andpastoralists were conducted in 2017 to augment the policy analysis. The paperreports that the provisions of the ECOWAS Transhumance Protocol, like thepossession of the International Transhumance Certificate as a mandatory entryrequirement, have not been implemented in Nigeria.